Daily ups and downs in adolescents' depressive symptoms: The role of daily self‐criticism, dependency and basic psychological needs. (4th August 2021) - Vandenkerckhove, Beatrijs; Soenens, Bart; Flamant, Nele; Luyten, Patrick; Campbell, Rachel; Vansteenkiste, Maarten
ABSTRACT: Introduction: Although associations between Blatt's personality dimensions of self‐criticism and dependency and adolescents' depressive symptoms are well‐established, only few studies have examined associations between these variables at the level of daily, within‐person fluctuations. Moreover, our understanding of the mechanisms underlying this personality vulnerability to depressive symptoms is limited. Therefore, we studied (a) daily fluctuations in both personality and depressive symptoms over a 7‐day period and (b) the possible interplay between daily variations in personality vulnerability, need‐based experiences (as conceptualized in Self‐Determination Theory), and depressive symptoms. This interplay was examined in terms of both a mediational and a moderating role of the need‐based experiences. Methods: Participants were 121 Belgian adolescents ( M age = 15.81; SD age = 1.50; 52 % male) who completed questionnaires tapping into daily self‐criticism, dependency, need‐based experiences, and depressive symptoms every evening during seven consecutive days. Results & conclusions: Multilevel analysis revealed that self‐criticism and dependency fluctuated substantially on a daily basis. These daily fluctuations in personality were related to daily fluctuations in depressive symptoms, with daily variation in need‐based experiences mediating these associations. We found no evidence for interactions between personality and the need‐based experiences. The findings underscore the importance of considering daily fluctuations in individuals' personality vulnerability and point to the explanatory role of need‐based experiences in the relation between personality and depressive symptoms on a daily basis.